Shown the Ecua-door. (Economist, 2019)
The article reports on the criminal prosecution of Julian Assange, co-founder of nonprofit WikiLeaks, due to rape allegations made against him in Stockholm, Sweden and his publication of American secrets through WikiLeaks. Topics discussed include his connection with American soldier Chelsea Manning, two legal challenges facing Assange, and remarks from British Labour leader Jeremy Corbyn.